Lexical Disambiguation in Verb Learning: Evidence from the Conjoined-Subject Intransitive Frame in English and Mandarin Chinese - Arunachalam, Sudha; Syrett, Kristen; Chen, YongXiang (Frontiers in Psychology, 2016)
When presented with a novel verb in a transitive frame (X is Ving Y), young children typically select a causative event referent, rather than one in which agents engage in parallel, non-causative synchronous events. However, when presented with a conjoined-subject intransitive frame (X and Y are Ving), participants (even adults, as we show) are at chance. Although in some instances, children older than three can obtain above-chance-level performance, these experiments still appear to rely upon a within-experiment contrast with the transitive frame. This leads us to ask whether children can achieve success with the intransitive frame without such a contrast among constructions, and map a novel verb appearing in such a frame onto a non-causative meaning. Building on recent evidence that adverbial modifiers can support word learning for adjectives and for verbs (when both nominal and verbal candidate interpretations are considered) by directing children to a particular construal of a scene, we test the hypothesis that a semantically informative modifier, together, will provide children with additional lexical information that allows them to narrow down verb meaning and identify a non-causative interpretation for a novel verb appearing in the conjoined-subject intransitive frame. We find that for English-speaking children and adults it does, but only when together directly modifies the verb phrase, suggesting that participants appeal to compositionality and not just the brute addition of another word, even one that is semantically meaningful, to arrive at the intended interpretation. Children acquiring Mandarin Chinese, in contrast, do not succeed with the translation-equivalent of together (although adult speakers do), but they do with dōu (roughly, the distributive quantifier ‘each’). Our results point to a valuable source of information young children learning verbs: modifiers with familiar semantics.